The relationship between parenting and development of toddlers aged 1-5 years in the working area of Rawang public health center, Padang city - Miranie Safaringga; Uliy Iffah; Adinda Permata Sari (Universitas Andalas, 2020)
Children under five years of age when the increase in body structure and function becomes more complex and the ability to move fine, fine motion, language, and independence. The number of children under five who do not develop according to their age is triggered by parental care, where this care aims to meet the basic needs of toddlers so that they can grow and develop more optimally. The purpose of this study was to determine the relationship between parenting and the development of children aged 1-5 years in the working area of Puskesmas Rawang, Padang City. This research uses quantitative design with a cross section. This research was conducted in the working area of Puskesmas Rawang, Padang City. Data collection was carried out in March 2020. The sample of this study is mothers who have children aged 1-5 years who are in the working area of Puskesmas Rawang, Padang City, amounting to 79 people. The technique used in this study is proportional random sampling, for data collection using a questionnaire. The results of this study obtained 79 respondents consisting of mothers and toddlers with an average age of 12-24 months. Descriptively democratic parenting has a proportion of under five development in accordance with the highest value, namely 95.6% while authoritarian is 11.5%. Democratic parenting style affects the optimal development of toddlers.